2018
DOI: 10.1002/slct.201800363
|View full text |Cite
|
Sign up to set email alerts
|

Optoelectronic Properties of Supramolecular Aggregates of Phenylalanine Conjugated Perylene Bisimide

Abstract: Perylene derivatives exhibit good optoelectronic properties and in order to augment it, the self‐assembly of phenyl alanine conjugated with perylene bisimide (PBI) would be a good motif because of excellent self‐organizing power of both the components. So we have synthesized N, N’‐di((S)‐1‐carboxylphenylalanine)‐3,4:9,10‐ perylenetetracarboxyl bisimide (PPA) and have studied its self‐organization in different organic solvents. Microscopic images reveal the formation of vesicles cast from chloroform. There is a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 47 publications
0
8
0
Order By: Relevance
“…The photophysical studies of PPAL and PPAD exhibit different concentration‐dependent characteristics in chloroform solutions of the compounds. The UV–Vis spectra of both dilute PPAL and PPAD solutions exhibit three absorption maxima at 459 nm, 490 nm, and 526 nm in chloroform at a concentration of 1.5 × 10 −5 mM (Figure a). These peaks arises due to the vibrational fine structure of S 0 to S 1 electronic transitions which correspond to the π–π* transition of the perylene compounds, respectively .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The photophysical studies of PPAL and PPAD exhibit different concentration‐dependent characteristics in chloroform solutions of the compounds. The UV–Vis spectra of both dilute PPAL and PPAD solutions exhibit three absorption maxima at 459 nm, 490 nm, and 526 nm in chloroform at a concentration of 1.5 × 10 −5 mM (Figure a). These peaks arises due to the vibrational fine structure of S 0 to S 1 electronic transitions which correspond to the π–π* transition of the perylene compounds, respectively .…”
Section: Resultsmentioning
confidence: 99%
“…Photoluminescence (PL) spectra of chloroform solutions of both PPAL and PPAD are recorded at different concentration by exciting the molecules at λ max , 490 nm. Both the enantiomer exhibit emission bands at 544, 579, and 623 nm at low concentration (7 × 10 −6 mM) shown in Figure b.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, the NMR data indicated a large degree of aggregation in DMSO for all three PDI–peptide derivatives, although the absorption and the fluorescence spectra were both characteristics of soluble and monomeric PDIs [ 58 ]. In another study, it was reported that the relatively polar nature of chloroform, in contrast to THF and DMF, facilitates the formation of intermolecular H-bonding of PDI–[F] 2 , which ultimately leads to J -aggregates [ 59 ]. In chloroform, PDI-[F] 2 assembled into vesicular suprastructures through the formation of right-handed helix, involving intermolecular H-bonding in lateral and π–π stacking in longitudinal growth directions.…”
Section: Peptide-pdi Bioconjugatesmentioning
confidence: 99%
“…Numerous studies have shown that the concentration of peptide-PDI conjugates can also influence their self-assembly as well as the final supramolecular architecture by modulating enthalpically and/or entropically driven self-recognition processes. Interestingly, it was shown that the symmetrical PDI-[F] 2 derivative exhibited distinct concentration-dependent photophysical properties in different organic solvents, such as THF, DMF, and CHCl 3 [ 59 ]. Increasing PDI–[F] 2 concentration from 0.45 mM to 14.6 mM in CHCl 3 caused a 43 nm red shift of the fluorescence emission peak, indicative of formation of J-aggregates.…”
Section: Peptide-pdi Bioconjugatesmentioning
confidence: 99%
“…This is in good agreement with the aforementioned experimental results (Figure 2C), the reduction of the PBI aggregation state is correlated to an enhancement of fluorescence emission. In presence of phenylalanine, indeed, the π-π stacking among D-PBI moieties is most probably reduced by the steric hindrance of the amino acid inserting within the aggregates, reducing the self-quenching events (Chal et al, 2018;Bettini et al, 2019). Then, the enhancement factor (EF) of D-PBI fluorescence (λ exc = 500 nm) in presence of phenylalanine at different concentrations was calculated as…”
Section: Disaggregation Process Of D-pbi Aqueous Solution In Presencementioning
confidence: 99%